1991
DOI: 10.1021/jf00002a019
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of hydrolysis products from 3-butenyl glucosinolate in rats

Abstract: While glucosinolate breakdown products occur only in trace quantities in rapeseed meal from European and North American oil mills, glucosinolate hydrolysis during processing in small South Asian oil mills is very significant. This paper reports a study of the toxicity of breakdown products from 3-butenyl glucosinolate, the major glucosinolate in South Asian rapeseed varieties. The compounds were administered to rats by stomach intubation or intraperitoneal injection. l-Cyano-3,4-epithiobutane was found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Toxicities of organic nitriles vary but are generally lower than cyanide salts and hydrogen cyanide. Toxicity seems particularly pronounced towards the liver (hepatotoxic) and kidney (Dietz et al 1991;Duncan 1991;Fenwick et al 1983;Van Etten et al 1969). The LD 50 in rats for ethyl CN (propanenitrile) is 50-100 mg kg -1 (Sittig 1985); for 1-cyano-2-hydroxy-3-butene, values of 170 mg kg -1 and 200 mg kg -1 have been reported Tookey et al 1980).…”
Section: Allergenic Reactionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Toxicities of organic nitriles vary but are generally lower than cyanide salts and hydrogen cyanide. Toxicity seems particularly pronounced towards the liver (hepatotoxic) and kidney (Dietz et al 1991;Duncan 1991;Fenwick et al 1983;Van Etten et al 1969). The LD 50 in rats for ethyl CN (propanenitrile) is 50-100 mg kg -1 (Sittig 1985); for 1-cyano-2-hydroxy-3-butene, values of 170 mg kg -1 and 200 mg kg -1 have been reported Tookey et al 1980).…”
Section: Allergenic Reactionsmentioning
confidence: 98%
“…For 1-cyano-3,4 epithiobutane, mortality in rats occurred after ingestion of 180 mg kg -1 (Dietz et al 1991) and an LD 50 of 109 mg kg -1 has been reported ). An LD 50 range of 178-240 mg kg -1 was estimated for 1-cyano-2-hydroxy-3,4 epithiobutane (Van Etten et al 1969).…”
Section: Allergenic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments of Munchmeyer et al (1974) pigs avoided myrosinase-treated high-glucosinolate rapeseed meal diets. More recently in low-glucosinolate rapeseed products the glucosinolate degradation by endogenous myrosinase activation increased diet acceptance by rats (Dietz et al 1991) or pigs (Schone et al 19946).…”
Section: Rapeseed: Iodine: Thyroid Hormones: Pigsmentioning
confidence: 99%
“…At a 0.1% level of addition, mixed nitriles brought about poor growth as well as liver and kidney lesions in rats after a 106 days of feeding (14). However, despite severe effects of 4, 5-epithiopentane nitrile on animals, no toxic effects were registered after the administration of its polymerized form (16). The toxic and goitrogenic effects of glucosinolate breakdown products were generally more pronounced in non-ruminants.…”
Section: Toxicity Antinutritional and Possible Beneficial Effects Ofmentioning
confidence: 94%